Pregnancy-Related Disorders and Intrauterine Impaired Lung Development - Zulhadji, Harry Agustio; Yunus, Faisal; Rasmin, Menaldi; Saroyo, Yudianto Budi; Amien, Bagus Radityo (Faculty of Medicine Universitas Airlangga, 2024)
Various pregnancy-related disorders are known to affect fetal lung development negatively. During pregnancy, chronic nutrition and/or oxygen limitation is known to impede lung maturation and induce airway and lung abnormalities. Structural abnormalities and reduced lung function may be evident immediately after birth, persist, or develop with age. The expansion of the fetal lung, fetal breath movements, fetal lung growth, alveolarization, blood-air barrier, extracellular matrix (ECM), airways, surfactant system, and lung immune function are all affected by nutritional limitations during pregnancy. Gestational hypoxia disrupts fetal lung development, which manifests as morphological and functional pulmonary abnormalities. Additionally, intrauterine growth restriction (IUGR), preeclampsia (PE), exposure to air pollution, and smoking are known to interfere with embryonic lung development. Birth defects, such as bronchopulmonary dysplasia, as well as chronic obstructive pulmonary disease (COPD), can be caused by abnormalities in pregnancy. Adequate nutrition, avoidance of smoking, and watchful monitoring and intervention during pregnancy should be promoted to prevent chronic lung disease of the newborn, child, and adult.